Efficacy of acupuncture in animal models of various ovarian dysfunctions: a systematic review and meta-analysis - Zhao, Yuemeng; Lan, Ying; Liu, Liying; Hao, Jianheng; Wang, Haijun; Ji, Laixi (Frontiers in Medicine, 2024)
Objective This study aims to assess the comprehensive and integrated modulatory effects of acupuncture and electroacupuncture on various ovarian dysfunctions. Methods We systematically searched for articles on animal experiments related to polycystic ovary syndrome (PCOS), premature ovarian failure (POF), premature ovarian insufficiency (POI), and perimenopausal syndrome (PMS) across multiple databases, including PubMed, Web of Science, Cochrane Library, Embase, and four Chinese language databases. The search covered the period from inception to November 2023. We conducted a comparative analysis between the acupuncture group and the model group (untreated) based on eligible literature. Our primary outcomes encompassed serum sex hormones (Luteinizing hormone, Follicle-stimulating hormone, Testosterone, Estradiol, Progesterone, and Anti-Müllerian hormone) and ovarian weight. Dichotomous data were synthesized to establish the relative risk (RR) of notable post-treatment improvement, while continuous data were pooled to determine the standardized mean difference (SMD) in post-treatment scores between the groups. Statistical analyses, including sensitivity analysis, Egger's test, and the trim-and-fill method, were executed using Stata 15.0 software. Results The meta-analysis encompassed 29 articles involving a total of 623 rats. In comparison to rat models of PCOS, the experimental group exhibited a reduction in serum levels of LH, T and LH/FSH ratio. However, no statistically significant differences were observed in AMH, FSH, E2 levels, and ovarian weight between the two groups. In the ovarian hypoplasia model rats, both acupuncture and electroacupuncture interventions were associated with an increase in E2 levels. However, the levels of LH and FSH did not exhibit a significant difference between the two groups. Conclusions Acupuncture or electroacupuncture facilitates the restoration of ovarian function primarily through the modulation of serum sex hormones, exerting regulatory effects across various types of ovarian dysfunction disorders. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022316279